12=-4(-6p-3)

Rewrite the equation as -4(-6p-3)=12.

-4(-6p-3)=12

Divide each term in -4(-6p-3)=12 by -4.

-4(-6p-3)-4=12-4

Cancel the common factor of -4.

Cancel the common factor.

-4(-6p-3)-4=12-4

Divide -6p-3 by 1.

-6p-3=12-4

-6p-3=12-4

Divide 12 by -4.

-6p-3=-3

-6p-3=-3

Add 3 to both sides of the equation.

-6p=-3+3

Add -3 and 3.

-6p=0

-6p=0

Divide each term in -6p=0 by -6.

-6p-6=0-6

Cancel the common factor of -6.

Cancel the common factor.

-6p-6=0-6

Divide p by 1.

p=0-6

p=0-6

Divide 0 by -6.

p=0

p=0

Solve for p 12=-4(-6p-3)